Utilization of Geographic Information Systems for Natural Disaster Mitigation: A Literature Study with a Focus on the City of Medan - Muhammad Abdillah Syam; Fahmi Aditya Abdi; Harits Al Khosyi; J. Prayoga; Abdi Sugiarto (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This article discusses the role of Geographic Information Systems (GIS) in disaster mitigation, especially in the city of Medan, Indonesia, which faces a high risk of flooding. With its flat geographical characteristics and dense urbanization, Medan is vulnerable to various types of flooding, including shipping and local flooding. GIS serves as an important tool in the collection, analysis, and visualization of spatial data, which supports an understanding of disaster-prone areas and better decision-making. This study identifies that the use of GIS can increase the accuracy of identifying disaster-prone locations by 25% compared to traditional methods. In addition, the integration of advanced technologies such as big data and virtual reality can enrich spatial analysis and improve the effectiveness of mitigation planning. However, challenges in the implementation of GIS, such as the availability of accurate data and the need for human resource training, need to be addressed to maximize its potential in disaster risk management.